Exploring Traumatic Brain Injuries and Aggressive Antisocial Behaviors in Young Male Violent Offenders - Katzin, Samuel; Andiné, Peter; Hofvander, Björn; Billstedt, Eva; Wallinius, Märta (Frontiers in Psychiatry, 2020)
Background: Traumatic brain injury (TBI) is a major cause of disabilities and mortality worldwide, with higher prevalence in offender populations than in the general population. Previous research has strongly advocated increased awareness of TBI in offender populations. The aim of this study was to explore the prevalence and characteristics of TBI, and to investigate associations and interactions between TBI, aggressive antisocial behaviors, general intellectual functioning, and substance use disorders (SUD) in a well-characterized group of young violent offenders. Methods: The study investigated a cohort (n = 269) of 18–25-year-old male violent offenders in Sweden. Data on TBI (files + self-report), aggressive antisocial behaviors (Life History of Aggression), SUD (clinical interviews), and general intellectual functioning (General Ability Index, Wechsler Adult Intelligence Scales Third Edition) were collected between 2010 and 2012. Parametric (Student’s t-test) and non-parametric (Mann-Whitney U test, Spearman’s rho, χ2, Kruskal Wallis test) inferential statistics were applied and effect sizes reported. Results: TBI, both with and without loss of consciousness, was common, with 77.5% of the offenders reporting having suffered at least one TBI during their lifetime. TBI was associated with an increased occurrence of aggressive antisocial behaviors and SUD, and offenders with both TBI and SUD evidenced the largest amount of aggressive antisocial behaviors. No clinically meaningful associations were found between TBI and general intelligence. Effect sizes were in the small to medium range. Conclusions: Our study confirms an increased prevalence of TBI among young violent offenders compared to the general population, as well as associations between TBI, aggressive antisocial behaviors, and SUD. However, it provides no information on the severity of the TBI, nor on the causality of the demonstrated associations. Nevertheless, TBI, and possible related deficits, need to be considered in the assessment and treatment of young violent offenders.